1994
DOI: 10.1007/bf00194409
|View full text |Cite
|
Sign up to set email alerts
|

Food-induced increase in bioavailability of 5-methoxypsoralen

Abstract: 5-Methoxypsoralen (5-MOP) in combination with ultraviolet light exposure is used for the treatment of psoriasis. The effect of food on the pharmacokinetics of 5-MOP was evaluated in a randomized, crossover study in nine healthy subjects. Each subject received the tablets with a standardized breakfast or under fasting conditions. The food had a dramatic effect on the bioavailability of 5-MOP. Five of the subjects showed no measurable quantities (detection limit of the analytical technique 1 ng.ml-1) of 5-MOP wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The reason for this discrepancy could be due to the interaction between 5-MOP and other compounds in the extract matrix, the involvement of CYP enzymes or transporters [18], or due to drug precipitation in the GI tract. Numerous studies already reported large differences in oral absorption of 5-MOP due to the influence of formulation, particle size, and food effects in humans [19][20][21]. Our study was carried out in specific experimental conditions that avoided saturation and precipitation of the drug in the GI tract.…”
Section: Pharmacokineticmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this discrepancy could be due to the interaction between 5-MOP and other compounds in the extract matrix, the involvement of CYP enzymes or transporters [18], or due to drug precipitation in the GI tract. Numerous studies already reported large differences in oral absorption of 5-MOP due to the influence of formulation, particle size, and food effects in humans [19][20][21]. Our study was carried out in specific experimental conditions that avoided saturation and precipitation of the drug in the GI tract.…”
Section: Pharmacokineticmentioning
confidence: 99%
“…The same chemical-specific parameters, V ss /F, and intestinal permeability [27] information that were used in the rat model were also employed in the human PBPK model. After the model was extrapolated to humans, the predicted plasma concentrations in humans were validated by data from an experimental human pharmacokinetic study using a single oral dose of 1.2 mg/kg 5-MOP [21]. The exposure parameters determined from the PBPK model for 5-MOP were C max , t max , and AUC 0-16 h .…”
Section: Predictions Of Human Pharmacokinetics Using a Physiologicallmentioning
confidence: 99%
“…14,16 This enhanced dissolution rate in the presence of food may be the reason for the improved bioavailability observed after oral administration of several lipophilic drugs such as danazol, 17 itracanazole, 18 phytonadione, 19 5-methoxypsoralen. 20 The importance of physiologically relevant dissolution media in predicting the effect of food on the oral bioavailability of poorly soluble drugs has been emphasized in a recent review. 21 From the present study, it was clear that the inferior aqueous solubilities of 2 and 3 do not have as great an influence on their in vivo behavior, while their relative behavior in the presence of SIBLM reasonably predicted their in vivo behavior.…”
Section: Intravenous Administration Of Sodium Phenytoinsmentioning
confidence: 99%
“…Synthetic 5 -methoxypsoralen (bergapten) and 5 -and 8 -methoxypsoralen ( 5 -MOP; 8 -MOP ; xanthotoxin or methoxsalen) are widely used in the treatment of several skin disorders including psoriasis, conditions of skin depigmentation (such as leprosy, vitiligio, and leucoderma), mycosis fungoides, polymorphous dermatitis, and eczema (Musajo and Rodighiero, 1962 ;Scott, Pathak and Mohm, 1976 ;Van Scott, 1976 ;Pathak and Fitzpatrick, 1992 ;Chadwick et al , 1994 ;Ehrsson et al , 1994 ). However, the psoralens have been linked to a higher incidence of skin cancer (Musajo and Rodighiero, 1962 ;Scott, Pathak and Mohm, 1976 ;Van Scott, 1976 ;Stern et al , 1979 ;Grekin and Epstein, 1981 ) and other disorders such as sister chromatid exchange, gene mutation, and chromosomal aberrations in humans (Calzavara -Pinton et al , 1994 ).…”
Section: Psoralensmentioning
confidence: 99%